Life strategies of senior students as the ability to determine life purposes in modern circumstances - Marchenoka, Marina (Journal of Education Culture and Society, 2021)
Aim. The purpose of this article is to define the scientific paradigm in understanding of the concept of “life strategies of a person” and to conduct an empirical research in order to determine average values of indicators of life meaningfulness and subjective perception of the past, present, and future of senior students in Latvia. Methods. The research is based on the theoretical study of different conceptual approaches to comprehension of the phenomenon life strategies. Following research methods were used:1) Dmitry Leontiev’s test defined in “purpose life orientations” method (2006); for data acquisition; 2) a method “past, present and future” by Svetlana Mezhvidova (2001); 3) “colour test” method invented by Max Lüscher (1990). For processing data following analysis methods were used: processing of quantitative data by applying methods of mathematical analysis of statistical data as well as forecasting analytical methods.; Student’s t-test to compare medians of two independent samples; Spearman’s rank correlation; processing of qualitative data: content study and analysis, coding and processing of the obtained data; elucidation of quantitative and qualitative analysis. Results and conclusions. The theoretical analysis suggests that there is a definite scientific paradigm in understanding of the concept of life strategies of senior students. The empirical research showed that Latvian senior students have the average indicators of sense life orientations and that they are quite low according to statistically different scales. It characterises the insufficient process of setting and defining goals by senior students, the achievement of which would help them acquire the sense of meaningfulness, direction, and hopefulness of future life.